Community dwelling adults with a history of falling report lower perceived postural stability during a foam eyes closed test than non-fallers - Anson, E (Exp Brain Res, 2019)
Perceived postural stability has been reported to decrease as sway area increases on firm surfaces. However, changes in perceived stability under increasingly challenging conditions (e.g. removal of sensory inputs) and the relationship with sway area are not well characterized. Moreover, whether perceived stability varies as a function of age or history of falls is unknown. Here we investigate how perceived postural stability is related to sway area and whether this relationship varies as a function of age and fall history while vision and proprioceptive information are manipulated. Sway area was measured in 426 participants from the Baltimore Longitudinal Study of Aging while standing with eyes open and eyes closed on the floor and a foam cushion. Participants rated their stability [0 (completely unstable) to 10 (completely stable)] after each condition, and reported whether they had fallen in the past year. Perceived stability was negatively associated with sway area (cm(^)2) such that individuals who swayed more felt less stable across all conditions (β = −0.53, p < 0.001). Perceived stability decreased with increasing age (β = −0.019, p < 0.001), independent of sway area. Fallers had a greater decline in perceived stability across conditions (F = 2.76, p = 0.042) compared to non-fallers, independent of sway area. Perceived postural stability declined as sway area increased during a multi-sensory balance test. A history of falling negatively impacts perceived postural stability when vision and proprioception are simultaneously challenged. Perceived postural stability may provide additional information useful for identifying individuals at risk of falls.